The role of entrepreneurial orientation and innovation on employee job performance in Malaysian hotels / Siti Hajar Zakariah - Zakariah, Siti Hajar (2020)
As a service industry hospitality industry is with human dexterity. This state of affairs makes hotels continually creating and innovating products or services as an essential strategy to maintain a competitive edge. Despite the effects that entrepreneurial orientation (EO) and innovation has on performance, research appears to be divided into understanding entrepreneurial orientation. The purpose of this study is to examine the effect of EO and innovation dimensions and the moderating effect of training on employee job performance. Data relating to EO, innovation, training, and employee job performance were collected from one hundred and twenty F&B managers and supervisors working in four and five-star rating hotels in Selangor, Wilayah Persekutuan Kuala Lumpur and Wilayah Persekutuan Putrajaya, Malaysia. Internal consistency, indicator reliability, convergent validity, and discriminant validity was utilised to assess the reflective measurement model. Path analysis with the structural model was employed to test the proposed hypotheses. The results indicated EO partially affect employee job performance, with the path coefficient value is 0.147. Innovation was found to have a significant effect on employee job performance with the p= 0.344 and t-value of 3.577. Entrepreneurial orientation and innovation have strong support in a significant relationship (0: 0.557, t: 9.072, pO.OOO). It is noteworthy to highlight the moderating variable of training has a positive effect on the relationship between entrepreneurial orientation and employee job performance, p= 0.107 and t-value of 2.092. On the other hand, training has a negative effect on the relationship between innovation and employee job performance. Adding training as a moderating variable is new empirical evidence to the hospitality industry specifically in Malaysia. The findings would be able to assist hotel managers in improving the training programmes related to entrepreneurial orientation and reflect on the importance of innovation as an on-going event as compared to "a one-time process" that helps increase the employees' performance. EO which is at the infancy stage in Malaysia is seen to have a significant contribution in terms of proactiveness and autonomy given to subordinates. Hence, this study contributes to the body of knowledge by adding new guidelines or manual for employee in order to enhance their entrepreneurial orientation and innovation elements in their daily routine besides entrepreneurial training been given. This study also provide empirical evidence to the direct relationship between entrepreneurial orientation, innovation, and employee job performance.